Primary Care Doctors' Assessment of and Preferences on Their Remuneration - Stefanos Karakolias PhD; Catherine Kastanioti PhD; Mamas Theodorou PhD; Nikolaos Polyzos PhD (SAGE Publishing, 2017)
Despite numerous studies on primary care doctors' remuneration and their job satisfaction, few of them have quantified their views and preferences on certain types of remuneration. This study aimed at reporting these views and preferences on behalf of Greek doctors employed at public primary care. We applied a 13-item questionnaire to a random sample of 212 doctors at National Health Service health centers and their satellite clinics. The results showed that most doctors deem their salary lower than work produced and lower than that of private sector colleagues. Younger respondents highlighted that salary favors dual employment and claim of informal fees from patients. Older respondents underlined the negative impact of salary on productivity and quality of services. Both incentives to work at border areas and choose general practice were deemed unsatisfactory by the vast majority of doctors. Most participants desire a combination of per capita fee with fee-for-service; however, 3 clusters with distinct preferences were formed: general practitioners (GPs) of higher medical grades, GPs of the lowest medical grade, residents and rural doctors. Across them, a descending tolerance to salary-free schemes was observed. Greek primary care doctors are dissatisfied with the current remuneration scheme, maybe more than in the past, but notably the younger doctors are not intended to leave it. However, Greek policy makers should experiment in capitation for more tolerable to risk GPs and introduce pay-for-performance to achieve enhanced access and quality. These interventions should be combined with others in primary care's new structure in an effort to converge with international standards.